Carbon Inputs From Riparian Vegetation Limit Oxidation of Physically Bound Organic Carbon Via Biochemical and Thermodynamic Processes. Issue 12 (20th December 2017) - Graham, Emily B.; Tfaily, Malak M.; Crump, Alex R.; Goldman, Amy E.; Bramer, Lisa M.; Arntzen, Evan; Romero, Elvira; Resch, C. Tom; Kennedy, David W.; Stegen, James C.
Abstract: In light of increasing terrestrial carbon (C) transport across aquatic boundaries, the mechanisms governing organic carbon (OC) oxidation along terrestrial‐aquatic interfaces are crucial to future climate predictions. Here we investigate the biochemistry, metabolic pathways, and thermodynamics corresponding to OC oxidation in the Columbia River corridor using ultrahigh‐resolution C characterization. We leverage natural vegetative differences to encompass variation in terrestrial C inputs. Our results suggest that decreases in terrestrial C deposition associated with diminished riparian vegetation induce oxidation of physically bound OC. We also find that contrasting metabolic pathways oxidize OC in the presence and absence of vegetation and—in direct conflict with the "priming" concept—that inputs of water‐soluble and thermodynamically favorable terrestrial OC protect bound‐OC from oxidation. In both environments, the most thermodynamically favorable compounds appear to be preferentially oxidized regardless of which OC pool microbiomes metabolize. In turn, we suggest that the extent of riparian vegetation causes sediment microbiomes to locally adapt to oxidize a particular pool of OC but that common thermodynamic principles govern the oxidation of each pool (i.e ., water‐soluble or physically bound). Finally, we propose a mechanistic conceptualization of OC oxidation along terrestrial‐aquatic interfaces that can be used to model heterogeneous patterns of OC loss under changing land cover distributions. Key Points: Riparian vegetation protects bound‐OC stocks Biochemical processes associated with OC oxidation vary with vegetation state Common thermodynamic principles underlie OC oxidation regardless of vegetation state